Effective Business Communication Strategies to Improve Corporate Image in the Digital Era - Mustari; Rijal, Syamsu (CITACONOMIA, 2025)
This study aims to examine effective business communication strategies in shaping and enhancing corporate image in the digital era. Using a literature review method with a descriptive qualitative approach, the research explores various theories related to business communication, the role of digital media, participatory communication, and reputation management. The findings show that consistent, interactive, and responsive communication is essential in building public trust and strengthening corporate reputation. Social media plays a crucial role in creating consumer engagement, while participatory digital communication strategies enhance loyalty and foster positive public perception. These results highlight the importance of communication as a strategic tool in today's dynamic and transparent business environment.